Management of Chordoma and Chondrosarcoma with Fractionated Stereotactic Radiotherapy - Vasudevan, Harish N.; Raleigh, David R.; Johnson, Julian; Garsa, Adam A.; Theodosopoulos, Philip V.; Aghi, Manish K.; Ames, Christopher; McDermott, Michael W.; Barani, Igor J.; Braunstein, Steve E. (Frontiers in Surgery, 2017)
OBJECTIVE: To evaluate the efficacy and toxicity of fractionated stereotactic radiotherapy (FSRT) for chordoma and chondrosarcoma. METHODS: Twenty consecutive patients with a histopathologic diagnosis of chordoma (n=16) or chondrosarcoma (n=4) treated between 2010 and 2016 were retrospectively identified. All patients underwent FSRT in 5 fractions to a median dose of 37.5 Gy (range: 25-40 Gy) and followed with serial magnetic resonance imaging (MRI). Overall survival (OS), local recurrence free survival (LRFS), and event free survival (EFS) were estimated using the Kaplan-Meier method. RESULTS: With a median follow-up of 28 months after FSRT and 40 months after initial surgery, crude OS and LRFS were 90%. Nine patients (45%) reported grade 1-3 acute toxicity, and two patients (10%) experienced grade 4-5 late toxicity. One patient previously treated with proton therapy died from radiation vasculopathy nine months after FSRT. The use of FSRT for recurrent disease or in patients with prior radiation therapy was associated with significantly decreased EFS. CONCLUSIONS: FSRT for chordoma and chondrosarcoma is associated with high rates of overall survival and local control. Although many patients experience acute toxicity, there is a low incidence of late toxicity or irreversible treatment related morbidity despite the frequency of prior radiotherapy in this population. FSRT is an effective adjuvant or salvage treatment for chordoma and chondrosarcoma.